843 Risk factors for unintentional house fire incidents, injuries and deaths: a systematic review. (1st September 2016) - Turner, Samantha L; Johnson, Rhodri; Weightman, Alison L; Rodgers, Sarah E; Arthur, Geri; Bailey, Rowena; Lyons, Ronan A
Abstract : Background: Unintentional house fires appear to be reducing but remain a serious public health concern, disproportionately affecting certain groups in population. To ensure preventative measures reach those at greatest risk, it is vital that risk factors for unintentional fires are identified; particularly in light of recent funding cuts in many Fire Services across high-income countries. However, the last review to be conducted in this area was undertaken over 15 years ago. Methods: To synthesise the evidence on risk factors for unintentional house fires, a range of bibliographic databases and grey literature were searched until October 2015. Key journals and reference lists were also hand-searched. To ensure the magnitude of risk could be quantified for each factor, only those studies that contained a comparison group, and undertook appropriate statistical analyses were included. A best evidence synthesis was undertaken instead of a meta-analysis due to study heterogeneity. Results: This review identified 12 studies that investigated a variety of potential risk factors and outcomes that fulfilled the inclusion criteria. None of the identified studies were deemed high quality, but the available evidence suggests the following factors may be associated with fire risk: age, gender, socio-economic status, race/ethnicity, disability, household ownership, household composition, property characteristics, smoking, alcohol/drug use, fire safety practices and marital status. It also appears that whilst older and disabled residents are more likely to suffer an injury or fatality in the event of a fire; they are less likely to ignite a fire in the first instance. Conclusions: There is a surprising paucity of high quality studies examining risk factors for house fire incidents, injuries and deaths. Further high quality studies, adopting standardised methods are required to permit synthesis, and to develop a firmer understanding of unintentional house fire risk factors.